OVERCRIMINALIZATION DALAM PERATURAN PEMERINTAH NOMOR 9 TAHUN 1975 - Adi Syahputra Sirait (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2020)
This paper aims to analyze and explain how the state criminalizes through government regulation Number 9 of 1975 concerning the Implementation of Law Number 1 of 1974 concerning Marriage which is basically an administrative law, therefore it is not allowed to regulate or create constitutional rules. and contains criminal provisions that have the potential to cause overcriminalization. As a normative legal research, this paper uses a conceptual and statutory approach (State Approach). The results of this study concluded that overcriminalization is the criminalization of acts that are not reprehensible and do not fulfill the principle of lex certa, as well as criminalization of pure administrative violations and their threats are not proportional to the seriousness of the alleged offenses.